Does the Nominal Exchange Rate Regime Affect the Real Interest Parity Condition? - Christian Dreger (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The real interest partity (RIP) condition combines two cornerstones in international finance, uncovered interest parity (UIP) and ex ante purchasing power parity (PPP). The extent of deviation from RIP is therefore an indicator of the lack of product and financial market integration. This paper investigates whether the nominal exchange rate regime has an impact on RIP. The analysis is based on 15 annual real interest rates and covers a long time span, 1870-2006. Four subperiods are distinguished and linked to fixed and flexible exchange rate regimes: the Gold Standard, the interwar float, the Bretton Woods system and the current managed float. Panel integration techniques are used to increase the power of the tests. Cross section correlation is embedded via common factor structures. The results suggest that RIP holds as a long run condition irrespectively of the exchange rate regimes. Adjustment towards RIP is affected by the institutional framework and the historical episode. Half lives of shocks tend to be lower under fixed exchange rates and in the first part of the sample, probably due to higher price flexibility before WWII. Although barriers to foreign trade and capital controls were substantially removed after the collapse of the Bretton Woods system, they did not lead to lower half lives during the managed float.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C32; F21; F31; F41; 330; Real interest parity; nominal exchange rate regime; panel unit roots; common factors